1998
DOI: 10.1112/s0024611598000586
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Metrics on the Unit Ball in Euclidean Space

Abstract: We study densities ρ on the unit ball in euclidean space which satisfy a Harnack type inequality and a volume growth condition for the measure associated with ρ. For these densities a geometric theory can be developed which captures many features of the theory of quasiconformal mappings. For example, we prove generalizations of the Gehring‐Hayman theorem, the radial limit theorem and find analogues of compression and expansion phenomena on the boundary. 1991 Mathematics Subject Classification: 30C65.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 16 publications
4
76
0
Order By: Relevance
“…Our final theorem is an extension of the Radial Limit Theorem [1,Theorem 4.4]. This result also relates to [3,Remark 1.3] where the size of the boundary set E ⊂ ∂B n where the conformal deformation mapping can "blow up" was estimated.…”
Section: Theorem 12 Letγ ⊂ B N Be a Curve Joining 0 And ξ So That Lmentioning
confidence: 66%
See 4 more Smart Citations
“…Our final theorem is an extension of the Radial Limit Theorem [1,Theorem 4.4]. This result also relates to [3,Remark 1.3] where the size of the boundary set E ⊂ ∂B n where the conformal deformation mapping can "blow up" was estimated.…”
Section: Theorem 12 Letγ ⊂ B N Be a Curve Joining 0 And ξ So That Lmentioning
confidence: 66%
“…In [1, Theorem 3.1] it is namely shown that assuming a Harnack inequality and (1.1) guarantees that the geodesic arc in B n essentially is the shortest path with respect to ρ-distance between any x and y in B n . Nevertheless, the authors of [1] do not comment in any way whether (1.1) is the best possible upper bound for the volume growth or not.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations